Muscular Dystrophy Surveillance Tracking and Research Network (MD STARnet): Case Definition in Surveillance for Childhood-Onset Duchenne/Becker Muscular Dystrophy - Mathews, Katherine D. (2010)
The Muscular Dystrophy Surveillance Tracking and Research Network (MD STARnet) is a multisite collaboration to determine the prevalence of childhood-onset Duchenne/Becker muscular dystrophy and to characterize health care and health outcomes in this population. MD STARnet uses medical record abstraction to identify patients with Duchenne/Becker muscular dystrophy born January 1, 1982 or later who resided in one of the participating sites. Critical diagnostic elements of each abstracted record are reviewed independently by ≥4 clinicians and assigned to 1 of 6 case definition categories (definite, probable, possible, asymptomatic, female, not Duchenne/Becker muscular dystrophy) by consensus. As of November 2009, 815 potential cases were reviewed. Of the cases included in analysis, 674 (82%) were either “definite” or “probable” Duchenne/Becker muscular dystrophy. These data reflect a change in diagnostic testing, as case assignment based on genetic testing increased from 67% in the oldest cohort (born 1982–1987) to 94% in the cohort born 2004–2009.